Methods of Da’wat in the Achieving freedom "Specific Study from the life of Sahabah kiram (May Allah bless them and grant them peace): حصول آزادی میں اسلوب ِدعوت "صحابہ کرام رضوان اللہ علیہم اجمعین کی زندگی سے اختصاصی مطالعہ " - Ikram, Zabrijah; Mehmood, Hafiz Tariq; Khan, Dr. Muhammad Muavia (Al Khadim Research Journal of Islamic Culture and Civilization, 2023)
The Calling position of the Sahaba,(May Allah bless them and grant them peace), in the pursuit of independence, the preaching role and their personal and collective struggle and struggle, is the prominent part of the history of Islam, without which the meaning of Islamic history seems vague and illusory. The work of preaching the call for freedom was not an easy morsel for them to swallow easily, but this work proved to be an iron pick for these brave Mujahideen, in this way they endured as many hardships as they endured. And all the sufferings have been endured with a smile. There are two basic roles in the style of da’wah: one is the supplicant and the other is the invitee. Therefore, the success of the da’wa depends entirely on the personality of the da’ee, because no matter how attractive the subjects of the da’wa may be, if the da’ee’s method of da’wah is not proper and he/she does not have the ability to explain the matter to the opponent by adopting different styles according to the situation. If it does, there is no chance of success. what is not understood from one side, the same thing when it comes out in another way, it gets into the heart. The success of the preacher is only in the fact that friends and enemies all cry out that he has paid the right to communicate.according to its special miraculous style, the Holy Qur’an has described the principles of da’wah in these words: “(O Prophet) Call people to the path of your Lord with wisdom and good advice and debate with them in a very good manner”. Three basic principles of the style of invitation to religion have been described: wisdom, good preaching and good argument. If the life of the Prophet (peace and blessings of Allah be upon him) is studied as a claimant of Islam, it can be clearly felt that he (peace and blessings of Allah be upon him) deviated from these principles while fulfilling the duty of calling and preaching. No, and the same principles can be seen in the Da’wah character of the trained Companions of the Holy Prophet (peace be upon him). How unfit is an untrained Da’i for the Da’wat. https://doi.org/10.5281/zenodo.10519324